PRIORITY ANALYSIS OF RURAL IN JERUJU BESAR VILLAGE, SUNGAI KAKAP DISTRICT, KUBU RAYA REGENCY - Heri, Azwansyah; Komala, Erwan; Nurlaily, Kadarini S; Sumiyattinah, Sumiyattinah; Elsa, Mukti Tri (Fakultas Teknik Universitas Tanjungpura, 2022)
The priority scale of village infrastructure development is important in order to provide greater value for the community. Data were collected through observation, and interviews. Data analysis includes prioritization, and infrastructure improvement strategies. This study resulted in priority areas for the agricultural and education sectors, namely hamlet of Karya Tani and hamlet of Karya Bersama with accessibility values of 9.03 and 8.67. hamlet of Karya Mulia has priority in the health, clean water, and electricity sectors with an accessibility value of 7.86; 8.09, and 6.40. Increased accessibility in the agricultural sector in the form of repairing irrigation, sluice gates, and procurement of water pumping machines, in the education and health sectors in the form of yard casting, in the clean water sector installing PDAM water networks or well water treatment, and the electricity sector by increasing the service life of electricity.